Volumetric contact theory to electrical contact between random rough surfaces. (August 2021) - Ta, Wurui; Qiu, Suming; Wang, Yulong; Yuan, Jinyu; Gao, Yuanwen; Zhou, Youhe
Abstract: A volumetric contact theory is developed that is valid for investigating electro-mechanical contact properties between random rough surfaces. The theory includes the contact resistance formula and the elastic and elastoplastic electrical contact models. They do not need to pre-suppose a certain contact pattern, and are not limited to the assumption that the real contact area is much smaller than the nominal contact area. The real contact area between rough surfaces is obtained by calculating the three-dimensional equivalent contact volume, which is a bridge connecting contact resistance and contact deformation. The theory can be used to predict the change of contact resistance with squeezing load in the elastic and plastic ranges. It also shows that the contact volume is the key to the contact problem between random rough surfaces. The models quantify the electrical contact behavior between rough surfaces using the void and real contact volume ratio, which provides a new perspective for understanding the electro-mechanical coupling mechanism between rough surfaces. Highlights: A new theory is developed for studying contact behaviors between rough surfaces. The theory quantify the contact behavior using the void and contact volume ratio. The contact volume is the key to the contact problem between rough surfaces.